Website Dinamis Experience Center Untuk Menampilkan Interplay Di Bidang Infrastructure Service & Reseach (ISR) PT. Telkom Indonesia, TBK - Yenni Fatman; Pujawati Pujawati; Fawzan Nurshehha (Departement of Mathematics Education, 2023)
PT. Telkom Indonesia in an effort to transform into a digital telecommunication company, TelkomGroup implements a customer-oriented company business and operational strategy. One of them is by creating a Website Experience Center to display the interplay made in the Infrastructure Service & Research IRA Unit. In making it the author uses the Extreme Programming Method which is considered appropriate because it is an adaptive and flexible method in its stages. The results obtained after analysis and design, as well as implementation of the Website Experience Center, Website Experience can be made as expected even though there are several obstacles in its manufacture. Where it is necessary to use adequate devices in its manufacture in order to produce maximum results as well